2023
DOI: 10.1007/s11764-023-01382-5
|View full text |Cite
|
Sign up to set email alerts
|

Supporting the return to work of breast cancer survivors: perspectives from Canadian employer representatives

Abstract: Pur pose A significant proportion of women with breast cancer want to RTW (return to work) after treatment. Employers play a key role in facilitating RTW for these employees who face distinct challenges. However, the portrait of these challenges remains to be documented from the perspective of employer representatives. The purpose of this article is to describe the perceptions of Canadian employer representatives regarding the management of the RTW of BCSs (breast cancer survivors). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Survivors reported that they felt they were a burden on the system and that too much was being expected of them. The level of support provided by the employer can be crucial in returning to the workplace in that it can either promote or hinder an employee's return and ability to function [37,38]. Other studies reinforce this finding, showing that impatience on the part of a manager can have a negative impact on cancer survivors' performance and meaning of work, when they return to work [6,18,39,40].…”
Section: Discussionmentioning
confidence: 99%
“…Survivors reported that they felt they were a burden on the system and that too much was being expected of them. The level of support provided by the employer can be crucial in returning to the workplace in that it can either promote or hinder an employee's return and ability to function [37,38]. Other studies reinforce this finding, showing that impatience on the part of a manager can have a negative impact on cancer survivors' performance and meaning of work, when they return to work [6,18,39,40].…”
Section: Discussionmentioning
confidence: 99%
“…According to a summary of qualitative studies, ‘offering work flexibility’ and ‘offering work accommodations’ are among the managerial interventions found to be most effective in fostering RTW [ 19 ]. From the point of view of employers, adopting a humanistic management style by offering flexibility and increased accommodation to BCSs could be the best strategy [ 20 ].…”
Section: Introductionmentioning
confidence: 99%